Estudio del principio de integración de países en la UNASUR y su relación con la constitución del Ecuador - Maldonado Valencia, Christian Fernando (2011)
The creation of new International Organizations is included in the organization of the law’s system of each member countries. These organizations generate international relations those need to be administrated by an appropriate legal framework through which they may be promoted and fully controlled. According to this idea, the legislation about integration in the world and from our country, it is urgent the implementation of clearer rules and regulations in the Ecuadorian legal system. The aim will be to achieve the fundamental tenets of the doctrine Legal Science: "The law must go hand in hand with the development of peoples who leads". Readers of this thesis will be able to understand the main problems and loopholes in socio- economic regulations signed in the International Agreement between member countries of the Union of South American Nations (UNASUR). The main characteristics of this agreement and the way it is linked with the Ecuadorian Constitution will be also explained in this work. The current regulations will be described and the legal regulations according to the new circumstances will be suggested for Ecuador. This thesis has four chapters those describe different parameters: CHAPTER ONE: Union of South American Nations (UNASUR), concepts, objectives, membership, operations, etc. CHAPTER TWO: Ecuador as member of the UNASUR, social and economic implications. CHAPTER THREE: Detailed explanation of the International Agreement principles as well as the features, rights and obligations at UNASUR. CHAPTER FOUR: The UNASUR and the Andean Community (CAN), the regional impact of UNASUR.